2019
DOI: 10.1111/liv.14171
|View full text |Cite
|
Sign up to set email alerts
|

Patient‐reported outcomes in patients chronic viral hepatitis without cirrhosis: The impact of hepatitis B and C viral replication

Abstract: Background & Aim Chronic infections with hepatitis B or C (HBV and HCV) are associated with adverse clinical outcomes and patient‐reported outcomes (PROs). The aim is to compare PRO scores in patients with chronic HBV and HCV without advanced liver disease before and after suppression/clearance of their infection. Methods Patients with HCV and HBV infection prior to initiation of antiviral treatment and after viral suppression/eradication completed PRO questionnaires. Results We included 132 patients with HBV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 39 publications
0
21
0
Order By: Relevance
“… 14 , 15 A recent study found that chronic hepatitis B (CHB) and CHC patients had worse PRO scores when they tested positive for viraemia, than after viral suppression or sustained virological response, when there was a substantial improvement. 16 …”
Section: Introductionmentioning
confidence: 99%
“… 14 , 15 A recent study found that chronic hepatitis B (CHB) and CHC patients had worse PRO scores when they tested positive for viraemia, than after viral suppression or sustained virological response, when there was a substantial improvement. 16 …”
Section: Introductionmentioning
confidence: 99%
“…The CLDQ instrument is a widely used, fully validated liver‐specific instrument to assess HRQL in patients with chronic liver disease. Since its development and validation, CLDQ and its HCV and NASH versions (CLDQ‐HCV and CLDQ‐NASH) have been used worldwide and translated into multiple different languages 14,15 . To date, CLDQ and its specific versions have been the most commonly used liver‐specific instruments worldwide 9,14,15 .…”
Section: Discussionmentioning
confidence: 99%
“…Since its development and validation, CLDQ and its HCV and NASH versions (CLDQ‐HCV and CLDQ‐NASH) have been used worldwide and translated into multiple different languages 14,15 . To date, CLDQ and its specific versions have been the most commonly used liver‐specific instruments worldwide 9,14,15 . Given the burden of HBV and the significant uptake of validated CLDQ in different patient populations across the world, a more refined version of the CLDQ applicable to patients with HBV will be valuable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The psychosocial harms described in this review exist despite the availability of treatment and vaccination. These interventions can sometimes reduce patient worry and stigma [98,99], but this is…”
Section: Conflicts Of Interestmentioning
confidence: 99%